A survey of public elementary school libraries in Marikina City based on the standards set by the Department of Education, Culture and Sports - Torres, Maria Donavie B.; Dizon, Leticia B. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1998)
The Department of Education, Culture and Sports issued a bulletin pertaining to the minimum library standards recommended for elementary, secondary, and tertiary levels. This study was conducted to find out the state of public elementary school libraries in Marikina City, based on these set of standards. The fourteen schools included in this study were Barangka, Calumpang, Capitan Moy, Concepcion, Fortune, H. Bautista, Leodegario Victorino, Marikina, Nangka, Parang, San Roque, St. Mary, Sto. Nino, and Tanong Elementary School. These were assessed during the descriptive survey method. Data were gathered through questionnaires and interviews.
Analysis was made based on the following: 1) physical set-up; 2) furniture and equipment; 3) collection; 4) librarian's tools; 5) materials/supplies; 6) management of the school library; and 7) personnel/staff.
Findings showed that none of the fourteen public elementary school libraries meet the recommended minimum standards. Not one school was able to meet the standard library floor area. Library furniture and equipment in each library are not enough to be able to comply with the DECS standards. Ratio of 1 book to 10 pupils is not applicable to almost all of the school libraries studied because of limited collection. There were only two school that catalog their library resources using the Dewey Decimal Classification, which is the only library tool available.
Management of the school library consists of selection and acquisition, organization of library materials, weeding, and library guidelines and procedures. Only two schools have a selection and acquisition policy while three practice weeding. Nine out of fourteen schools have established and written library guidelines and procedures.
Among the fourteen librarians, there were only two who have acquired units in Library Science and none serves full time. The school principal does all the decision-making for the library.
This study revealed that only one school is aware of the DECS Bulletin. Yet, it could not comply due to budget constraints and lack of classrooms. These two factors, and the absence of a full time librarian, are found to be the problems of the rest of the schools in this study.
Recommendations for this study focused on the factors that could improve the library services. It includes allotment of enough budget from the local government, hiring of a full-time librarian, inclusion of library orientation in the school curriculum, regular evaluation of library resources and services, and monitoring from DECS regarding compliance to standards.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)
Keywords: Elementary school libraries -- Philippines -- Marikina City; Elementary school libraries -- Standards. -- Philippines